1966
DOI: 10.1002/ijc.2910010106
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical changes associated with the development of resistance to 5‐azacytidine in AKR leukemic mice

Abstract: Resistance to 5-azacytidine, a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1967
1967
2008
2008

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Of particular interest are the membrane transporters that mediate cellular drug uptake. Early studies in a leukemic mouse model showed a connection between azacytidine resistance and impaired uptake of uridine and cytidine, which supported an important role of cellular transport mechanisms in mediating drug effects 33. However, the role of transport processes in the treatment with azanucleosides has not been characterized on the molecular level yet.…”
Section: Cellular Uptake Of Azanucleosidesmentioning
confidence: 99%
“…Of particular interest are the membrane transporters that mediate cellular drug uptake. Early studies in a leukemic mouse model showed a connection between azacytidine resistance and impaired uptake of uridine and cytidine, which supported an important role of cellular transport mechanisms in mediating drug effects 33. However, the role of transport processes in the treatment with azanucleosides has not been characterized on the molecular level yet.…”
Section: Cellular Uptake Of Azanucleosidesmentioning
confidence: 99%
“…The enzyme has attracted considerable interest because of its pharmacological importance in experimental cancer chemotherapy with uridine (Pasternak et al, 1961;Reichard et al, 1962) and cytidine (Vesely et al, 1970) analogues that are converted into biologically active 5'-phosphates. During the development of resistance towards uridine and cytidine antimetabolites uridine kinase activity has been found in some cases to be partially deleted, and this impairment is often considered as the metabolic deviation underlying the change to resistance (Brockman, 1963).…”
Section: Discussionmentioning
confidence: 99%
“…Previously we have studied uridine kinase in mouse and adult rat liver under different experimental conditions. Although the activity of the enzyme from livers of leukaemic mice made resistant to 5-azacytidine is diminished in comparison with its counterpart from livers of the parental leukaemic line of mice (Vesely et al, 1970), the activity of uridine kinase from normal adult rat liver is markedly enhanced after the administration of 5-azacytidine (Cihak et al, 1972). Both enzyme preparations are more stable on heating than the respective controls.…”
mentioning
confidence: 99%
“…It was observed that resistance of 5-AzCR was achieved rapidly in the AK mouse leukemia and was cross-resistant to 5-fluorouraciI. In the resistant tumors there was less inhibition of the incorporation of orotic acid into the nucleic acids, less uridine kinase, and less uridine phosphorylase activity than in the sensitive cells (132). 5-Iodo-2'-deoxyuridine (I UdR).-The synthesis of this nucleoside (X, Fig.…”
Section: Purine Analoguesmentioning
confidence: 96%